FEMINIZATION OF MEDICAL EDUCATION IN PAKISTAN - Muhammad Akram Malik (Journal of University Medical & Dental College, 2020)
Recent proposal of Pakistan Medical & Dental Council to reserve 50% seats for boys & Girls in admissions to Medical Colleges of Pakistan has generated a lot of controversy and debates in all literary circles of the country. Some groups are advocating 50/50 quota while others are opposing it considering it against human rights and woman rights.